Development of Electrolyte Box to Improve Student Learning Outcomes at SMAN 2 Sungai Ambawang - Jurniawan, Ferdy; Kurniati, Tuti; Kurniasih, Dedeh (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The problems that arise in class X MIA SMA Negeri 2 Sungai Ambawang related to the learning process have not carried out practicum activities due to limited facilities and infrastructure at school. This study aims to develop Electrolyte Box media on electrolyte and nonelectrolyte solution materials that are valid, practical and effective. This type of research is Research and Development (R&D) ADDIE model. The sampling technique used is purposive sampling technique. The sample in this study amounted to 27 students of SMA Negeri 2 Sungai Ambawang. Validity is measured from the validator's assessment using the validation sheet, practicality is measured from the learner response questionnaire, then effectiveness is measured based on the pretest and posttest results of students. The data analysis technique is descriptive statistics. The results of the validity of the material and media aspects of the Electorlyte Box are 0.83 (very valid) and 0.79 (valid), respectively. The practicality test results in the initial and main field trials obtained very practical criteria with a value of 98.43% and 96.30% respectively. The effectiveness aspect in the initial and main field trials was 0.73 and 0.71 with high criteria. Therefore, the learning media in high school that has been developed is suitable for use as learning media.